Fostering Akidah Akhlak Values through the Kampung Warna Interactive Storybook in Islamic Elementary Education - Yumna Yumna; Nana Fauzana Azima; Nurul Majeedah Hamdan; Preexcy B. Tupas; Herli Indrayani (Universitas Negeri Padang, 2025)
This study developed and evaluated an interactive digital storybook titled Kampung Warna as a learning tool for moral and character education in Islamic elementary schools. It responds to the need for engaging, age-appropriate resources to support Akidah Akhlak learning in early grades. The research assessed the e-book’s validity, practicality, and effectiveness for grade 2 students. Using a development research approach, the process included expert validation, teacher and student trials, and pre- and post-test evaluations. Data were collected from 80 students across four Madrasah Ibtidaiyah in West Sumatra through validation forms, questionnaires, and learning outcome tests. The data were analyzed using descriptive statistics, expert validation procedures, practicality assessment analysis, and normalized gain scores to evaluate the effectiveness of the learning media. Results showed that Kampung Warna achieved a validity score above 90%, with practicality scores of 95.71% from teachers and 94.75% from students. The normalized gain reached 78.42%, indicating high effectiveness. The Kampung Warna interactive storybook is highly valid, practical, and effective for Akidah Akhlak learning. It enhances student engagement, supports teachers in conveying moral values, and significantly improves learning outcomes with high effectiveness confirmed through statistical analysis.